Macroeconomic and Social Determinants of International Migration Inflows: A Semiparametric Panel Data Analysis in OECD Countries (Third Sector Social Economic Review, 2026)
This paper examines the socioeconomic determinants of international immigration inflows across 26 OECD countries over the period 2010–2022, which is chosen to ensure data consistency and to capture the post-global financial crisis era as well as subsequent global economic shocks. The main contribution of the study lies in applying a semi-parametric panel data model that allows for potential non-linear relationships between migration and macroeconomic as well as human capital indicators. By relaxing the restrictive assumptions of conventional linear models, this approach provides a more flexible framework for analyzing migration dynamics. The empirical findings indicate that income differentials, unemployment rates, and labor market conditions constitute key drivers of immigration inflows. Results from the semi-parametric estimations show that economic growth and increases in real wages are associated with higher immigration inflows, whereas rising unemployment and inflation exert a discouraging effect on migration. In addition, improvements in educational attainment—measured by the mean years of schooling of the population aged 25 and over—are found to significantly promote immigration inflows. Overall, the findings suggest that immigration inflows are closely linked to labor market conditions, macroeconomic stability, and human capital accumulation. In this context, migration policies that are responsive to labor market demand and supportive of skilled immigration may contribute to a more effective management of migration flows. Moreover, aligning education policies with migration strategies and structuring legal migration channels in accordance with labor market needs may strengthen the long-term economic impacts of migration. Nevertheless, as the analysis is limited to OECD countries and focuses exclusively on immigration inflows, the results should be interpreted with caution when considering different institutional and economic contexts.
Keywords: International Migration; Economic Growth; Semiparametric Panel Data Models; Unemployment; Education Policies